Partial Deregulation and Competition: Effects on Risky Mortgage Origination - Di Maggio, Marco; Kermani, Amir; Korgaonkar, Sanket (Management Science, 2019)
We exploit the preemption of national banks from state laws against predatory lending by the Office of the Comptroller of the Currency (OCC) as a quasi-experiment to study the effect of deregulation and its interaction with competition on the supply of complex mortgages. Following the preemption ruling, national banks significantly increased their origination of loans with prepayment penalties relative to national banks in states without anti-predatory-lending laws. We highlight a competition channel: in counties where OCC-regulated lenders had larger market shares, non-OCC-regulated lenders responded by increasing their supply of contracts with riskier features, such as deferred amortization, which were not restricted by the state anti-predatory-lending law. Non-OCC lenders were able to lure borrowers into these higher-margin contracts by increasing their appeal with teaser rates. This paper was accepted by Tyler Shumway, finance.